The Aging of the “Youngest People in Europe” - Morse, Donald E. (Hungarian Journal of English and American Studies, 2020)
Book review: Ingman, Heather. Ageing in Irish Writing: Strangers to Themselves. Cham: Palgrave Macmillan, 2018. 209 pages. ISBN 978 3 319 96429-4. Hb. €74.89.